Assessing the biomechanics of scheuermann’s kyphosis affected thoracolumbar spine in forward flexion at the tissue-level using a finite element model - Wan, Chunli; Shen, Xiaowen; Wu, Xixi; Yu, Cui; Shao, Yi; Zhang, Ruiping; Shang, Jiao; Li, Jianan; Zhang, Yuting; Li, Yongqiang (Scientific reports, 2025)
Thoracolumbar kyphosis (TLK) secondary to Scheuermann’s disease often leads to low back pain, which may be related to altered biomechanical properties of the spine. However, There is a lack of biomechanical studies in the literature that comprehensively evaluate tissue-level stresses and strains in the thoracolumbar spine affected by Scheuermann’s kyphosis, particularly during functional motions such as forward flexion. This study analyzed biomechanical changes during forward flexion in TLK patients using musculoskeletal dynamics and finite element modeling. Twenty TLK patients and twenty healthy individuals were recruited. Kinematic data (joint angles), kinetic data (joint reaction forces and moments), and electromyographic (EMG) data were collected at different bending angles using Vicon 3D motion capture and surface electromyography. Physiologic motions captured from in vivo experiment was simulated using OpenSim, with inverse dynamics and optimization used to calculate vertebral joint angles, muscle forces, and intervertebral reaction forces, serving as boundary conditions for ANSYS finite element models. Subject-specific finite element models for both groups were constructed in ANSYS using computed tomography (CT) DICOM files. The CT-based finite element models were used to compute von Mises stress distributions—a mechanical parameter indicating combined tissue stress and potential risk of overload—in the vertebral body, intervertebral discs, and articular cartilage at different forward flexion angles under the applied loadig conditions. At different forward bending angles, TLK patients exhibited high stress distribution in the L1-S1 segment vertebral articular processes. Compared with healthy individuals, the stress distribution in the S1 segment was uneven, with peak stress reaching up to to 2.8 times higher (180% increase) than that of healthy individuals. TLK patients exhibit stress concentration in the annulus fibrosus region of the intervertebral disc, while the stress distribution in the nucleus pulposus region is relatively uniform. The peak stress in the intervertebral disc during different movements can be up to 2.33 times higher (133% increase) than in healthy individuals. In TLK patients, stress concentration was observed in the articular cartilage of all segments except for the L5/S1 segment. The peak stress in the articular cartilage during different movements was up to 12.02 times higher (1,102% increase) than in healthy individuals. These results suggest that TLK patients experience elevated and uneven spinal tissue stress during forward flexion, which may contribute to increased risk of degeneration and back pain.